2021
DOI: 10.1186/s12934-020-01497-9
|View full text |Cite
|
Sign up to set email alerts
|

Rhamnolipid the Glycolipid Biosurfactant: Emerging trends and promising strategies in the field of biotechnology and biomedicine

Abstract: Rhamnolipids (RLs) are surface-active compounds and belong to the class of glycolipid biosurfactants, mainly produced from Pseudomonas aeruginosa. Due to their non-toxicity, high biodegradability, low surface tension and minimum inhibitory concentration values, they have gained attention in various sectors like food, healthcare, pharmaceutical and petrochemicals. The ecofriendly biological properties of rhamnolipids make them potent materials to be used in therapeutic applications. RLs are also known to induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(75 citation statements)
references
References 94 publications
1
72
0
2
Order By: Relevance
“…This makes surfactants one of the most versatile chemicals for industrial processes [ 7 ]. The most commonly used surfactants are of chemical origin, but their toxic nature, low degradation rate, and high persistence power limit their frequent use in the food, cosmetics, and pharmaceutical industries [ 8 ]. Surfactants of microbial origins have several advantages over synthetic or chemical surfactants: higher temperature tolerance, stability in pH variation, high salinity tolerance, higher degradation rate, less toxicity, and better selectivity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This makes surfactants one of the most versatile chemicals for industrial processes [ 7 ]. The most commonly used surfactants are of chemical origin, but their toxic nature, low degradation rate, and high persistence power limit their frequent use in the food, cosmetics, and pharmaceutical industries [ 8 ]. Surfactants of microbial origins have several advantages over synthetic or chemical surfactants: higher temperature tolerance, stability in pH variation, high salinity tolerance, higher degradation rate, less toxicity, and better selectivity [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, the stronger reduction in surface tension together with the higher yield of biosurfactants in the HVGO culture showed that HVGO was a better substrate for biosurfactants production than glucose [ 8 , 19 , 20 , 21 , 22 ]. Rhamnolipids are known to reduce the surface tension to values between 28 and 30 mN/m [ 7 ]. The minimum surface tension value measured in the HVGO culture (26 mN/m) is relatively lower than reported values for the AK6U strain on either HVGO (30.6 mN/m) or organosulfur compounds (30–33 mN/m) [ 19 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, biosurfactants have a broad range of environmental and industrial applications such as bioremediation, soil washing, biocontrol and application of fertilizers, enhanced oil recovery, cosmetics, pharmaceuticals, antimicrobial agents, foods and beverages, etc. [ 3 , 4 , 5 , 6 , 7 ]. Biosurfactants are structurally diverse and can be composed of proteins, peptides, fatty acids, phospholipids and carbohydrates.…”
Section: Introductionmentioning
confidence: 99%
“…B. coagulans MA-13 is also able to ferment sugars derived from pre-treatment of lignocellulose to lactic acid in the presence of inhibitors; in fact, it was proved that this bacterium can grow and ferment in bioreactors containing 95% hydrolysate [ 144 ]. At the same time, seed culture pre-adaptation of B. coagulans MA-13, before simultaneous saccharification and fermentation step, can improve the production of lactic acid; again, it has a pool of interesting intra- and extracellular enzymes with glycosyl hydrolyzing activities that make B. coagulans MA-13 useful for increasing nutritional value of food [ 145 , 146 ].…”
Section: Lignocellulosic Biomassesmentioning
confidence: 99%